1998
DOI: 10.1074/jbc.273.27.16678
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metal-activated Pyridoxal Enzyme with a Unique Primary Structure, Low Specificity d-Threonine Aldolase fromArthrobacter sp. Strain DK-38

Abstract: The gene encoding low specificity D-threonine aldolase, catalyzing the interconversion of D-threonine/Dallo-threonine and glycine plus acetaldehyde, was cloned from the chromosomal DNA of Arthrobacter sp. strain DK-38. The gene contains an open reading frame consisting of 1,140 nucleotides corresponding to 379 amino acid residues. The enzyme was overproduced in recombinant Escherichia coli cells and purified to homogeneity by ammonium sulfate fractionation and three-column chromatography steps. The recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…4). This spectral shift has been observed both in free (41,42) and enzyme-bound PLP (27,43) when reacting with L-cysteine and has been ascribed to the appearance of a stable complex containing a thiazolidine ring.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4). This spectral shift has been observed both in free (41,42) and enzyme-bound PLP (27,43) when reacting with L-cysteine and has been ascribed to the appearance of a stable complex containing a thiazolidine ring.…”
Section: Discussionmentioning
confidence: 96%
“…4A). However, since L-cysteine is also known to react with some pyridoxal phosphate enzymes (27), we inspected the spectral changes that occur in the visible region upon the addition of L-cysteine. As observed in Fig.…”
Section: Fig 2 Effect Of Divalent Cationsmentioning
confidence: 99%
“…Our biochemical analysis showed that chDSD can use not only Zn 2ϩ but also Mn 2ϩ for the catalytic reaction, the latter ion being able to coordinate N and S atoms. Interestingly, D-threonine aldolases, which belong to fold-type III PLP-dependent enzymes, preserve the same metal-binding motif of His-X-Cys/Asp in the C-terminal region as found in chDSD and require an Mn 2ϩ ion for the ␣-elimination of D-threonine to produce acetoaldehyde and glycine (12). Although the crystal structure of D-threonine aldolases has not been solved, the present crystal structure of chDSD suggests that the hydroxyl group of the substrate D-threonine coordinates the Mn 2ϩ in the active site.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found recently that, in the chicken brain, D-serine is degraded mainly by a D-serine dehydratase (DSD) 4 (10), which catalyzes the ␣,␤-elimination of water from D-serine to form pyruvate and ammonia. In addition, we have found that the chicken DSD (chDSD) has a primary structure similar to those of metal-activated D-threonine aldolases (11)(12)(13), which are fold-type III PLP-dependent enzymes (14), and is distinct from a well known metal-independent bacterial DSD (dsdA) belonging to the foldtype II PLP-dependent enzyme family (14,15). Interestingly, a fold-type III family protein coded by gene YGL196W of Saccharomyces cerevisiae was recently identified as a zinc-dependent DSD (scDSD) (16).…”
mentioning
confidence: 99%
“…There have been some reports on PLPdependent aldolases. [13][14][15][16] It is not clear that the Arthrobacter aldolase requires PLP as a coenzyme, because the transaminase in the reaction mixture also requires PLP as a cofactor. Further characterization, cloning, and expression of the aldolase are in progress.…”
Section: Effect Of the Cultivation Time Of A Simplex Aku 626 On The mentioning
confidence: 99%